Antibiotic prescribing for upper respiratory infections among children in rural China: a cross-sectional study of outpatient prescriptions. Issue 1 (1st January 2017) - Zhang, Zhitong; Hu, Yanhong; Zou, Guanyang; Lin, Mei; Zeng, Jun; Deng, Simin; Zachariah, Rony; Walley, John; Tucker, Joseph D.; Wei, Xiaolin
ABSTRACT: Background : Overuse of antibiotics contributes to the development of antimicrobial resistance. Objective: This study aims to assess the condition of antibiotic use at health facilities at county, township and village levels in rural Guangxi, China. Methods: We conducted a cross-sectional study of outpatient antibiotic prescriptions in 2014 for children aged 2–14 years with upper respiratory infections (URI). Twenty health facilities were randomly selected, including four county hospitals, eight township hospitals and eight village clinics. Prescriptions were extracted from the electronic records in the county hospitals and paper copies in the township hospitals and village clinics. Results: The antibiotic prescription rate was higher in township hospitals (593/877, 68%) compared to county hospitals (2736/8166, 34%) and village clinics (96/297, 32%) ( p < 0.001). Among prescriptions containing antibiotics, county hospitals were found to have the highest use rate of broad-spectrum antibiotics (82 vs 57% [township], vs 54% [village], p < 0.001), injectable antibiotics (65 vs 43% [township], vs 33% [village], p < 0.001) and multiple antibiotics (47 vs 15% [township], vs 0% [village], p < 0.001). Logistic regression showed that the likelihood of prescribing an antibiotic was significantly associated with patients being 6–14 years old compared with being 2–5 years old (adjusted odds ratio [aOR] = 1.3, 95% CI 1.2–1.5), and receiving care at township hospitals compared with county hospitals (aOR = 5.0, 95% CI 4.1–6.0). Prescriptions with insurance copayment appeared to lower the risk of prescribing antibiotics compared with those without (aOR = 0.8, 95% CI 0.7–0.9). Conclusions: Inappropriate use of antibiotics was high for outpatient childhood URI in the four counties of Guangxi, China, with the highest rate found in township hospitals. A significant high proportion of prescriptions containing antibiotics were broad-spectrum, by intravenous infusion or with multiple antibiotics, especially at county hospitals. Urgent attention is needed to address this challenge.